ANALISIS PERKEMBANGAN KONDISI KESEHATAN KEUANGAN DAERAH MELALUI PENGUKURAN INDIKATOR KONDISI KEUANGAN PERMENDAGRI NO 19 TAHUN 2020 (STUDI KASUS KOTA PROBOLINGGO TAHUN 2017-2020) - Karisma Karisma; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to show it based on measurements of financial position indicators of Permendagri Number 19 of 2020, indicators of short-term solvency and long-term solvency have a trend that is still fluctuating but not too significant and the ratio value is close to or exceeds number 1 so that it indicates that the City of Probolinggo is still able to deal with matters related to operational expenses and obligations, both long term and short term. Then related to the solvency indicators of the Probolinggo city service, there is a trend that tends to increase every year, meaning that the expenditures spent, especially those related to serving the community by the Probolinggo City government, are getting better, however, this assessment indicator should also be applied to assess accuracy in terms of service delivery to the community. While related to financial conditions before and during the pandemic, Pprobolinggo City’s income tends to decrease overall compared to the previous Covid-19 pandemic, the decline was due to transfer income originating from balancing funds and transfer income from the provincial government.Keywords : Indicators of Conditions Finance, Local Government, Permendagri No 19 of 2020, Dimensions